Warrior Deity from Hadrian’s Wall: Possible Representations of Cocidius in Rock Art of Northern England - Namirski, Cezary (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2025)
The article aims to analyse the phenomenon of uninscribed rock carvings in Northern England depicting warrior figures. The carvings, found as rock art in the landscape, as well as in other contexts, are likely of Romano-British origin. A possible link to the cult of Cocidius, a native Celtic deity worshipped mainly by soldiers of the Roman army (especially the auxiliaries) on Hadrian’s Wall and in the surrounding areas, is explored. Various forms of evidence are considered, including epigraphic dedications to Cocidius, depictions on silver tablets from Bewcastle Roman Fort, the distribution of rock carvings, and the characteristics of military religion in Roman Britain.